2016
DOI: 10.1002/bit.25956
|View full text |Cite
|
Sign up to set email alerts
|

Fast plasmid based protein expression analysis in insect cells using an automated SplitGFP screen

Abstract: Recombinant protein expression often presents a bottleneck for the production of proteins for use in many areas of animal‐cell biotechnology. Difficult‐to‐express proteins require the generation of numerous expression constructs, where popular prokaryotic screening systems often fail to identify expression of multi domain or full‐length protein constructs. Post‐translational modified mammalian proteins require an alternative host system such as insect cells using the Baculovirus Expression Vector System (BEVS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This led to a saturation of the scattered light signal, even at low cell densities, and consequently false cell count estimates. A previous study demonstrated that the scattered light signal directly correlates with a cell density of up to 3 × 10 6 cells mL −1 using this shaking speed 15 . As the µ-bioreactor was established 16 as a screening tool for bacterial cultivation with cell densities up to 10 g L −1 , cell densities in standard BEVS cultivations should not lead to saturation of the light scattering signal.…”
Section: Calibration Of the Light Scatter Signalmentioning
confidence: 85%
“…This led to a saturation of the scattered light signal, even at low cell densities, and consequently false cell count estimates. A previous study demonstrated that the scattered light signal directly correlates with a cell density of up to 3 × 10 6 cells mL −1 using this shaking speed 15 . As the µ-bioreactor was established 16 as a screening tool for bacterial cultivation with cell densities up to 10 g L −1 , cell densities in standard BEVS cultivations should not lead to saturation of the light scattering signal.…”
Section: Calibration Of the Light Scatter Signalmentioning
confidence: 85%
“…With the aid of genetic engineering, a desired gene cloned into a suitable expression vector can be overexpressed as a recombinant protein of interest [34]. Recombinant proteins can be expressed in cell cultures of bacteria [35], yeasts [36], mammalian cells [37,38], plants [39] and insects [40]. However, the prokaryotic systems remains the most attractive hosts due to their low cost, high productivity and rapid production rates [30].…”
Section: Production Of Recombinant Proteins In a Prokaryotic Exprementioning
confidence: 99%
“…In order to improve the throughput and sensitivity of detection of successful expression constructs, fast screening strategies using TGE combined with transactivation [29, 30] or the SplitGFP technology [31] have been established. These methods avoid the need to generate high amounts of different recombinant baculoviruses.…”
Section: Introductionmentioning
confidence: 99%